2020
DOI: 10.9734/ejmp/2020/v31i330217
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Aloysia citriodora Palau Using Different Cutting Types under Light Intensity

Abstract: Aims: The aim of this study was to evaluate the effect of types of cuttings and light intensity on cidró vegetative propagation. Place and Duration of Study: Medicinal Plants Garden, Federal University of Grande Dourados (UFGD), Dourados, state of Mato Grosso do Sul, Brazil, September to November 2016. Methodology: The experiment was carried out under two light conditions (shaded and full light), evaluating three types of cuttings (softwood, semi-hardwood and hardwood). Experimental design was a 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
1
1
Order By: Relevance
“…There are no reference standards in the literature regarding the ideal percentage between each organ of the plant, which may vary depending on several factors, such as the cultivated species, luminous preference, natural habitat, among other physiological aspects; but generally, most of the photoassimilates produced are directed to the development of the aerial part to regulate the biosynthesis of carbohydrates. Aloysia citriodora Palau seedlings in a shaded environment had lower allocation of biomass in the roots when using hardwood cuttings (Silva et al, 2020), different from what was observed for P. aculeata seedlings. Pearson's linear correlation analysis (r) showed a significant correlation (P ≤ 0.05) between number of sprouts and number of leaves (r = 0.94), root dry mass and root area (r = 0.85), total dry mass and aerial part dry mass (r = 0.95) and root/aerial part (R/Pa) and aerial part dry mass (r = 0.95) (Figure 6), these being of high positive magnitude, that is, the increase of a certain characteristic results in the increase of another.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…There are no reference standards in the literature regarding the ideal percentage between each organ of the plant, which may vary depending on several factors, such as the cultivated species, luminous preference, natural habitat, among other physiological aspects; but generally, most of the photoassimilates produced are directed to the development of the aerial part to regulate the biosynthesis of carbohydrates. Aloysia citriodora Palau seedlings in a shaded environment had lower allocation of biomass in the roots when using hardwood cuttings (Silva et al, 2020), different from what was observed for P. aculeata seedlings. Pearson's linear correlation analysis (r) showed a significant correlation (P ≤ 0.05) between number of sprouts and number of leaves (r = 0.94), root dry mass and root area (r = 0.85), total dry mass and aerial part dry mass (r = 0.95) and root/aerial part (R/Pa) and aerial part dry mass (r = 0.95) (Figure 6), these being of high positive magnitude, that is, the increase of a certain characteristic results in the increase of another.…”
Section: Resultscontrasting
confidence: 79%
“…The higher values are associated with a greater number of carbohydrate reserves contained in the cuttings of the hardwood portion (Silva et al, 2020), having an energy source to maintenance survival. According to these authors, Aloysia citriodora Palau seedlings propagated using the hardwood portion of the stake showed a higher survival.…”
Section: Resultsmentioning
confidence: 99%